Thermal conversion of polystyrene plastic waste to liquid fuel via ethanolysis. (1st November 2020) - Ahmad, Nauman; Ahmad, Nabeel; Maafa, Ibrahim M.; Ahmed, Usama; Akhter, Parveen; Shehzad, Nasir; Amjad, Um-e-salma; Hussain, Murid
Graphical abstract: Highlights: Polystyrene is liquefied in an autoclave batch reactor via ethanolysis. Effect of temperature, solvent to polystyrene mass ratio, and time are studied. The highest oil yield of 86.4% is obtained at optimum conditions. The oil product is characterized by several analysis devices to observe its quality. Comparative study of liquefaction and pyrolysis of polystyrene is conducted. Abstract: Since decades, one of the major troublesome environmental issue to the society is Polystyrene waste. Thermal conversion method can be used to transform the plastic waste into useful energy source. In this study, liquefaction technique using ethanol as a solvent was used to produce liquid fuel from polystyrene. The experiments were performed at different temperatures (290–370 °C), ethanol to polystyrene ratios (0.25:1–4:1) and reaction times (15–75 min) in an autoclave batch reactor. After characterization, quantitative and qualitative evaluation of liquid products; results showed that at temperature of 350 °C, ethanol to polystyrene ratio of 0.5:1 and reaction time of 60 min, highest liquid yield of 84.7 wt% was achieved. The viscosity, density, pH, calorific value and flash point of the oil product at this condition was 0.36 cP, 0.88 g/mL, 6.86, 40.91 MJ/kg and 55 °C respectively. Through GC–MS analysis, it was found that the oil product was mostly composed of aromatics, alkenes and alkyls; which made the liquid oil suitable to be used as fuel. In addition, comparative study was conducted by replacing ethanol with water as solvent under same conditions. Based on results, study proved ethanol to be better solvent than water which is commonly used in liquefaction process. Lastly, the liquid fuel produced is suitable to be used as alternative energy source for conventional fossil fuels.